2016
DOI: 10.1158/1940-6207.capr-16-0209
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inflammation in Cancer Prevention and Therapy

Abstract: Inflammation is associated with the development and malignant progression of most cancers. As most of the cell types involved in cancer associated inflammation are genetically stable and thus are not subjected to rapid emergence of drug resistance, the targeting of inflammation represents an attractive strategy both for cancer prevention and cancer therapy. Tumor extrinsic inflammation is caused by many factors, including bacterial and viral infections, autoimmune diseases, obesity, tobacco smoking, asbestos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
246
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(253 citation statements)
references
References 142 publications
4
246
0
3
Order By: Relevance
“…Low-grade chronic inflammation is a primary contributor to the onset and progression of chronic kidney disease 11,142,209,210 . Inflammation is a causal factor for cancer initiation, promotion, malignancy, and metastatic dissemination 211,212 . Depression is characterized by increased levels of pro-inflammatory cytokines and acute phase proteins in both peripheral blood and cerebrospinal fluid 213,214 .…”
Section: Consequences Of Inflammageing For Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-grade chronic inflammation is a primary contributor to the onset and progression of chronic kidney disease 11,142,209,210 . Inflammation is a causal factor for cancer initiation, promotion, malignancy, and metastatic dissemination 211,212 . Depression is characterized by increased levels of pro-inflammatory cytokines and acute phase proteins in both peripheral blood and cerebrospinal fluid 213,214 .…”
Section: Consequences Of Inflammageing For Cvdmentioning
confidence: 99%
“…The collective evidence suggests that chronic inflammation is a risk factor across multiple diseases, some of which are traditionally viewed as pathophysiologically unrelated, such as CVD 157,159,160,220 , diabetes 138,180,221 , chronic kidney disease 11,142,209 , cancer 211,212,222 , depression 13,143,217 , and dementia 12,139,223 . In addition, higher levels of inflammatory markers in blood are associated with a greater loss of muscle mass and strength, accelerated loss of mobility, lower-extremity performance and physical activity, and depression in older individuals 224228 , all of which are essential elements for defining frailty on the basis of the criteria most often used in the literature 229 .…”
Section: Inflammation and Age-related Frailtymentioning
confidence: 99%
“…This association provides rationale for the utility of anti-inflammatory therapies for CRC prevention (3). Indeed, epidemiological evidence has shown that long-term non-steroidal anti-inflammatory drug (NSAID) use correlates with reduced incidence of CRC including in patients without IBD (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cancer-intrinsic inflammation can be triggered by cancer-initiating mutations and can contribute to malignant progression through the recruitment and activation of inflammatory cells. Both extrinsic and intrinsic inflammation can result in immunosuppression, thereby providing a preferred background for tumor development [6,7].…”
Section: Resultsmentioning
confidence: 99%